Students’ Perception of Google Classroom in Teaching and Learning during Pandemic of Covid-19 - Ni Putu Juni Ari (Journal of Educational Study, 2021)
This study aimed to investigate the students ‘perception and challenge in learning by using Google Classroom especially in the current pandemic of Covid-19. The present study used a literature review as the design to collect the data. Related studies about students ‘perception and challenge on Google Classroom in teaching and learning were analyzed to be described in the present study. The finding of this study showed that students have positive perception toward the use of Google Classroom in learning and it was useful in teaching. However, students ‘accessibility and connectivity were the most challenging in learning through Google Classroom during the pandemic.